Dampak intensitas penggunaan media sosial terhadap minat baca mahasiswa - winarto, cleodora fitriana (Maliki Interdisciplinary Journal, 2026)
This research aims to analyze and measure the influence of the intensity of social media use on students’ reading interest. The background to the problem is driven by concerns about the decline in academic literacy culture and the increase in the duration of social media access. This study uses a qualitative approach using the literature review method with students as the study population. Studies show a negative and significant relationship between the intensity of social media use and reading interest. The more often students interact on social media and spend longer periods of time, the less interested they are in reading. The results show that a time displacement phenomenon occurs, where the time available for reading is allocated entirely to consuming social media content. Therefore, this research recommends the need for healthy time management and digital literacy interventions on the part of institutions and student self-awareness to balance online information consumption with in-depth literacy activities.